Hypomagnesaemic hypocalcaemia with hypokalaemia caused by treatment with high dose gentamicin. Issue 10 (October 1978) - Kelnar, C J; Taor, W S; Reynolds, D J; Smith, D R; Slavin, B M; Brook, C G
Abstract : A 12-year-old boy developed renal wasting of magnesium, calcium, and potassium, with secondary hypomagnesaemia, hypocalcaemia, and hypokalaaemia (without hyperaldosteronism) after treatment with 14 400 mg gentamicin over 4 months. Gentamicin should not be given for prolonged courses if less toxic antibiotics are suitable. If it used, plasma magnesium, calcium, and potassium levels should be monitored during and after treatment.